Revitalization Skywaklk Bandung 2021 Reviving The Urban Area â€œUrban Spaceâ€ in Bandung - Nurcahya, Yan; Hadiansyah, Tantan; Yosita, Lucy; Akbar, Adha Syahidil; Allatif, I Gilang Miftah; Hilmayani, Syalwa Linda (Universitas Pendidikan Indonesia, 2021)
Abstract - Skywalk Bandung is well known as a well-known city icon and as a new tourist area in the city of Bandung. Completed and inaugurated 2017 Skywalk Bandung is a mandatory destination for tourists to visit, because it was developed in the Cihampelas area which is an official tourist destination in Bandung. After 2 years of inauguration, the Bandung skywalk has experienced a decline in visitors since its inauguration. Changing the Cipaganti road to one lane, the adjacent Cihampelas road into one lane is the same as Cihampelas making an alternative for tourists to Bandung, changing through the Cihampelas street after traveling to the Lembang area. lane transfer to Jl. Cipaganti being a single lane, helping to deal with congestion and reducing tourists to Jl. Cihampelas, so the construction of the skywalk is less useful than its original purpose. Through the journal that we convey today, it is hoped that it can become a reference method that can be used by the Bandung city government to be able to revive the city facilities that are not functioning properly with the initial plan targeted by the Bandung City Government. Such projects require special attention and, as explained at the beginning, an integrated approach due to the need to manage a large number of urban structures and significant financial investments. The construction of the Skywalk phase II, which is still unfinished, is the main problem that results in the neglect of the initial target development goals of the Skywalk, the neglect of completion of the construction is a major part of the revitalization that must be done.